Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, dan Good Corporate Governance terhadap Intellectual Capital Disclosure - Wiwid Setyowati; Eny Kusumawati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Intellectual capital is the wealth of a company that is an intangible asset and is expressed willingly. The purpose of this study was to analyze the influence of profitability, leverage, company size, audit committee, and board of directors on intelectual capital disclosure. The population in this study are manufacturing company listed on the Indonesia Stock Exchange in 2016-2020. The sample was determined by purposive sampling technique and obtained a sample of 240 companies. This type of research is quantitative using secondary data obtained from the financial statements and annual reports of manufacturing companies. This research uses statistikal analysis by regression analysis. The results in this study are the board of directors had affect on intelectual capital disclosure. Leverage, the size of the company, the audit committee, and the board of directors had no affect on intelectual capital disclosure.